The Role of Urinary Extracellular Vesicles Sodium Chloride Cotransporter in Subtyping Primary Aldosteronism - Kong, Linghui; Tang, Xiaofeng; Kang, Yuanyuan; Dong, Lei; Tong, Jianhua; Xu, Jianzhong; Gao, Ping-jin; Wang, Ji-guang; Shen, Weili; Zhu, Limin (Frontiers in Endocrinology, 2022)
Background: Adrenal venous sampling (AVS) is recognized as the gold standard for subtyping primary aldosteronism (PA), but its invasive nature and technical challenges limit its availability. A recent study reported that sodium chloride cotransporter (NCC) in urinary extracellular vesicles (uEVs) is a promising marker for assessing the biological activity of aldosterone and can be treated as a potential biomarker of PA. The current study was conducted to verify the hypothesis that the expression of NCC and its phosphorylated form (pNCC) in uEVs are different in various subtypes and genotypes of PA and can be used to select AVS candidates. Methods: A total of 50 patients with PA were enrolled in the study. Urinary extracellular vesicles (uEVs) were isolated from spot urine samples using ultracentrifugation. NCC and pNCC expressions were tested in patients diagnosed with PA who underwent AVS. Sanger sequencing of KCNJ5 was performed on DNA extracted from adrenal adenoma. Results: pNCC (1.89 folds, P<.0001) and NCC (1.82 folds, P=0.0002) was more abundant in the uEVs in the high lateralization index (h-LI, ≥ 4) group than in the low LI (l-LI, < 4) group. Carriers of the somatic KCNJ5 mutations, compared with non-carriers, had more abundant pNCC expression (2.16 folds, P=0.0039). Positive correlation between pNCC abundance and plasma aldosterone level was found in this study (R = 0.1220, P = 0.0129). Conclusions: The expression of pNCC in uEVs in patients with PA with various subtypes and genotypes was different. It can be used as biomarker of AVS for PA subtyping.